Suitability of Substrate for Laboratory Studies with the Subterranean Termite Reticulitermes grassei (Clément) (Isoptera: Rhinotermitidae) - Gallardo, Patricia; Cardenas, Ana M; Murillo, Raquel (Sociobiology, 2016)
Two substrates, sand and vermiculite, were tested in rearing laboratory experiments with Reticulitermes grassei at different culture periods (2, 4 and 6 weeks). Although information is available regarding procedures to keep species of Reticulitermes in lab, none of them is referred to the Mediterranean termite R. grassei. The suitability of substratum was assessed in terms of survival of termites. The highest survival rate was in the experiment with sand and short-time duration, but after six weeks exposure, survival was significantly lower on this substrate. These differences among substrates were not significant for any of the treatments.